Acute pulmonary edema in the puerperium due to preeclampsia and severe mitral insufficiency: A case report - Castro-Galvis, Carlos Andrés (2025)
Acute pulmonary edema in the puerperium is a rare but serious complication, associated mainly with severe preeclampsia and, in some cases, mitral insufficiency. We present the case of a 34-year-old female patient, with no past medical history, who developed acute pulmonary edema in the immediate puerperium after a complicated vaginal delivery with severe preeclampsia and moderate to severe mitral insufficiency. Initially, the patient was treated with embolization due to vulvar hematoma, and subsequently admitted to intensive care for respiratory failure, hypertensive crisis and confirmed pulmonary edema. After ruling out pulmonary thromboembolism and diagnosing bilateral pleural effusion, treatment with intravenous Labetalol, furosemide and oxygen was initiated, resulting in clinical improvement. An echocardiogram revealed significant mitral insufficiency, while proteinuria confirmed the diagnosis of preeclampsia. Adjustment of antihypertensive treatment, which included carvedilol, contributed to a favorable evolution. The importance of presenting this case lies in the need for early diagnosis and multidisciplinary management in patients with severe preeclampsia and cardiac complications, highlighting the relevance of cardiovascular evaluation to prevent life-threatening complications during the puerperium.